is that really the answer because if not im slapping across you
The expression 3x + 3y is a linear combination of two variables, x and y, with coefficients 3. The answer to this expression depends on the specific values of x and y. If x = 2 and y = 4, then the answer would be 3(2) + 3(4) = 6 + 12 = 18. In general, the answer to 3x + 3y is 3 times the sum of x and y.
5x+3y
2x - 3y = 12When x = 0, y = -4, so that y-intercept is -4.2x - 3y = 122(0) - 3y = 12-3y = 12 (divide both sides by -3)y = -4When y = 0, x = 6, so that x-intercept is 6.2x - 3y = 122x - 3(0) = 122x= 12 (divide both sides by 2)x = 6
x + 3y = 2 2x - 3y = 22 Add the two equations: 3x = 24 Divide both sides by 3 to give x= 8. Substitue this value of x in the first equation to give 8 + 3y = 2 Subtract 8 from both sides: 3y = -6 Divide both sides by 3: y = -2 Solution: (X, y) = (8, -2)
x = 2.15 and y = 3.75
x = 3y x - 3y = 3y - 3y x - 3y = 3y - 3y x - 3y = 0
3y2 y x y = y2 3 x y2 = 3y2
-3xy
4xy²(3y-x)-2x²(x-3y)²=4xy²(x-3y)-2x²(x-3y)²=(x-3y)[4xy²-2x²(x-3y)²]=(x-3y)(4xy²-2x³+6x²y)=(x-3y)(-2x³+6x²y+4xy²)=-2x(x-3y)(x²-3xy-2y²)= -2x(x-3y)(x-y)(x-2y)
-3X - 3Y x 8
X + 3y - 2y + 3y = X + (3-2+3)y = X + 4y
(a + x - 3y)(a - x + 3y)
The expression 3x + 3y is a linear combination of two variables, x and y, with coefficients 3. The answer to this expression depends on the specific values of x and y. If x = 2 and y = 4, then the answer would be 3(2) + 3(4) = 6 + 12 = 18. In general, the answer to 3x + 3y is 3 times the sum of x and y.
If you mean: 4x+3y = -1 and x-3y = -34 then x = -7 and y = 9
-x+3y+6x-6y=5x-3y
-7
If x - 3y = 12, we can solve for x in terms of y: x = 12 + 3y. Then, to find xy, we multiply x by y: xy = y(12+3y) = 12y + 3y^2.